The Concept of Moral Education in Ibn Miskawaih's Perspective: A Philosophical Analysis of Tahdzib Al-Akhlak - Choirul Anam (Global Education Journal, 2025)
The moral crisis afflicting contemporary education demands the revitalization of a comprehensive concept of moral education. This study examines Ibn Miskawaih's thought on moral education through an in-depth analysis of the book Tahdzib al-Akhlaq wa Tathhir al-A’raq. This research is a library research study with a philosophical-analytical approach. Data were collected from the primary source of Tahdzib al-Akhlaq and relevant secondary sources, then analyzed using descriptive-analytical methods and content analysis. The research findings indicate that Ibn Miskawaih's concept of moral education is based on four cardinal virtues (al-fadha’il al-arba’ah): wisdom (al-hikmah), courage (al-syaja'ah), temperance (al-'iffah), and justice (al-'adalah). Miskawaih views morality as a state of the soul that can be changed through education and habituation (ta’wid). The proposed educational methods include the natural method (thariqun thabi'iy), habituation, exemplary conduct, and Riyadhah (spiritual training). The concept of the middle way (al-washath) becomes a fundamental principle in achieving moral virtues, integrating Aristotle's rational approach with Islamic shari’ah values. This research contributes to the development of Islamic education theory by offering a philosophical framework that integrates reason and revelation in character formation. The implication is that moral education must be designed holistically, considering the psychological, social, and spiritual dimensions of learners and creating a conducive environment that supports moral transformation.